The age of em : work, love, and life when robots rule the Earth - Hanson, Robin (Oxford University Press, 2016)
Robots may one day rule the world, but what is a robot-ruled Earth like? Many think that the first truly smart robots will be brain emulations or "ems." Robin Hanson draws on decades of expertise in economics, physics, and computer science to paint a detailed picture of this next great era in human (and machine) evolution - the age of em.